Association of Free Fatty Acid (FFA), Fatty Acid Binding Protein (FABP) and Adiponectin with Tumor Necrosis Factor-alpha (TNF-alpha) and Interleukin-6 (IL-6) Among Obese Non Diabetic Males - Yani Lina; Gatot Susilo Lawrence; Andi Wijaya (The Prodia Education and Research Institute (PERI), 2009)
BACKGROUND: The prevalence of obesity has increased dramatically in recent years. It is commonly associated with type 2 diabetes, coronary artery disease, and hypertension. White adipose tissue (WAT) is a major site of energy storage and is important for energy homeostasis. WAT has been increasingly recognized as an important endocrine organ that secretes a number of biologically active “adipokines”. The resultant higher FFA, FABP4, FABP5 concentration; and lower concentration of adiponectin is known to be correlated with inflammation. The aim of this study was to observe the correlation between FFA, FABP4, FABP5 and adiponectin with TNF-α and Interleukin-6 as markers of inflammation.METHOD: The study was observational with a cross sectional design. The analysis was done on 69 male subjects aged 30-60 years with non diabetic abdominal obesity which is characterized by waist circumference (WC) 98.7±6.5 cm and fasting blood glucose 87.1±9.7 mg/dL. FFA testing was performed by enzymatic colorimetric assay; whereas FABP4, FABP5, TNF-α, adiponectin and IL-6 were performed by ELISA. All statistical calculations were performed with the SPSS 11.5 statistical software package. We used the Pearson or Spearman’s rho correlation coefficient to assess the correlation between various anthropometric and biochemical measures. We also used path analysis Lisrel 8.30 for Windows.RESULT: This study revealed that there was no correlation between FFA, FABP4 and adiponectin with TNF-α and Interleukin-6, whereas there was correlation between FABP5 with TNF- and Interleukin-6. This study also showed there were correlations between WC and hsCRP (r=0.314, p=0.000), WC and IL-6 (r=0.276, p=0.022), FFA and FABP4 (r=0.263, p=0.029), FABP4 and WC (r=0.249, p =0.039), FABP4 and BMI (r=0.311, p=0.009), FABP5 and TNF- (r=0.408, p=0.000), FABP5 and FABP4 (r=0.296, p=0.014), FABP5 and Interleukin-6 (r=0.248, p=0.04), Adiponectin and HDL-Cholesterol (r=0.301, p=0.012).CONCLUSION: Abdominal obesity might contribute to inflammation in obese nondiabetic males. This study indicated that in abdominal obesity, FFA may induce inflammation through FABP4 and FABP5. Advancing our understanding of the function and measurement of FABP4 and FABP5 serum concentration will give insight into the clinical diagnosis of obesity-related metabolic disorders.KEYWORDS: Obesity, Waist Circumference, Free Fatty Acid (FFA), Fatty Acid Binding Protein (FABP), Adiponectin, TNF-α, Interleukin-6, Inflammation